The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1063/1.2717538
|View full text |Cite
|
Sign up to set email alerts
|

Regrowth-related defect formation and evolution in 1MeV amorphized (001) Ge

Abstract: Ge implanted with 1 MeV Si + at a dose of 1 ϫ 10 15 cm −2 creates a buried amorphous layer that, upon regrowth, exhibits several forms of defects-end-of-range ͑EOR͒, regrowth-related, and clamshell defects. Unlike Si, no planar ͕311͖ defects are observed. The minimal EOR defects are small dotlike defects and are very unstable, dissolving between 450 and 550°C. This is in contrast to Si, where the EOR defects are very stable. The amorphous layer results in both regrowth-related defects and clamshell defects, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 23 publications
0
19
0
Order By: Relevance
“…2 Recently Hickey et al reported on defect formation and evolution during regrowth of amorphized ion-implanted Ge. 3 They observed regrowth related defects in annealed 1 MeV Si implanted Ge. End of range defects were minimal and annealed out between 450 and 550°C while regrowth defects were more stable.…”
Section: Introductionmentioning
confidence: 99%
“…2 Recently Hickey et al reported on defect formation and evolution during regrowth of amorphized ion-implanted Ge. 3 They observed regrowth related defects in annealed 1 MeV Si implanted Ge. End of range defects were minimal and annealed out between 450 and 550°C while regrowth defects were more stable.…”
Section: Introductionmentioning
confidence: 99%
“…[14][15][16] Recently, some progress in understanding the role of self-interstitials in Ge came from investigations on the migration of B, whose diffusivity is the lowest among all the impurities in Ge.…”
Section: Introductionmentioning
confidence: 99%
“…It should be noted that no threading dislocations or regrowthrelated defects are observed comparing to Si self-ion implantation 14,19 or like recently observed in Ge when amorphized by Si ions where after 650 C anneal a high density of threading dislocations is still present. 20 Moreover, at the anneal temperatures used, no {311} defects are formed. In selfimplanted Si at RT or at 77 K, {311} defects are already formed after annealing at the end of range region.…”
Section: A Buried Amorphous Layermentioning
confidence: 99%
“…Lithiation will then rather easily lead to destabilization of the host Si network (i.e., amorphization) and subsequent formation of new Si x Li y alloy phases, accompanied with significant volume expansion. 25 Crystalline silicon amorphizes at a ratio of 0.3 Li atoms per Si atom, 26 which means for a local Li concentration of 1.5 Â 10 22 at/cm 3 , i.e., far from our implanted maximum of 2.5 Â 10 20 Li/cm 3 . Thus, in the first step of recrystallization, Li atoms must stay in interstitial position and should not play a significant role.…”
Section: A Buried Amorphous Layermentioning
confidence: 99%